The genetic diversity of multiple sclerosis risk among Hispanic and African American populations living in the United States. (October 2020) - Beecham, AH; Amezcua, L; Chinea, A; Manrique, CP; Rubi, C; Isobe, N; Lund, BT; Santaniello, A; Beecham, GW; Burchard, EG; Comabella, M; Patsopoulos, N; et al.
Background: Substantial progress has been made toward unraveling the genetic architecture of multiple sclerosis (MS) within populations of European ancestry, but few genetic studies have focused on Hispanic and African American populations within the United States. Objective: We sought to test the relevance of common European MS risk variants outside of the major histocompatibility complex ( n  = 200) within these populations. Methods: Genotype data were available on 2652 Hispanics (1298 with MS, 1354 controls) and 2435 African Americans (1298 with MS, 1137 controls). We conducted single variant, pathway, and cumulative genetic risk score analyses. Results: We found less replication than statistical power suggested, particularly among African Americans. This could be due to limited correlation between the tested and causal variants within the sample or alternatively could indicate allelic and locus heterogeneity. Differences were observed between pathways enriched among the replicating versus all 200 variants. Although these differences should be examined in larger samples, a potential role exists for gene–environment or gene–gene interactions which alter phenotype differentially across racial and ethnic groups. Cumulative genetic risk scores were associated with MS within each study sample but showed limited diagnostic capability. Conclusion: These findings provide a framework for fine-mapping efforts in multi-ethnic populations of MS.